Social security: reforming the reform (1999)
The proposals to modify the Law number 100 of 1993 that were presented in the regional forum on social security held in Bogotá at the beginning of 1999 are examined. Based on 53 documents, the different kinds of proposals are presented, as well as the tendencies underlying them and the coincidences and divergences that are found between the different acting parts in the social security system. The most frequent subjects, in which most of the proposals were inscribed, were the mechanisms for government control, the subsidized regimen, the benefit plans, the information system and social participation. An outline for the analysis of the main problems that are recognized by the different acting parts in the social security system is presented, with emphasis on the need for scenarios of debate where the bases for guaranteeing the right to integral social security are discussed.